Modelling of the Zakat payment behaviour in Aceh, Indonesia - Muammar Khaddafi, Mohd Heikal, Yuli Asbar,; Saputra, Jumadil; Ikhsan, Arfan (Opción, 2019)
This quantitative study aims to analyse the influence of behavioural factors, subjective norms, perception on behaviour control and past behaviour of traders in Lhokseumawe city on their interesting paying zakat of their trading (trade zakat). As a result, it shows that the interests will directly shape human behaviour, the Interests fulfils the criteria of Not Good becomes Good, while the Behavior of Paying Zakat indicates the changes from Not Good becomes Very Good. In conclusion, Interests in 3 dimensions include Continuity, Knowledge and Suggestion are in the category of Not Good to Good, which is dominantly shaped by Continuity dimensions.